Identifying the Employment and Population Centers at regional and metropolitan scale: The Case of Catalonia and Barcelona - Jaume Masip Tresserra (European Regional Science Association (ERSA), 2012)
Nowadays, the urban structure of the metropolitan areas has led to a polynucleated structure, breaking with the paradigm of the monocentric city. The specialized literature has studied this polynucleated structure by identifying the centers that are within of these urban areas. According to this objective, many approaches have used in order to identify these centers (sub-centres): by analyzing the employment or population density and by studying the mobility flows. In this paper, the employment and population centers in Catalonia and in the Barcelona Metropolitan Region are identified by taking into account a new mobility approach, focusing on the flows of workers and people. In doing so, this study has carried out a dynamic analysis: from 1981 to 2010 in the case of identifying population centers and from 1991 to 2001 in the case of detecting employment centers at the time that the functional and the administrative boundaries of the Barcelona Metropolitan Region has also taken into account. Then, the influence of these identified sub-centres on the urban spatial structure is analyzed by estimating the evolution of polycentricity level and their influence on the urban hierarchy. The results by having this dynamic perspective (1981-2010) and (1991-2001) suggest: a more polynucleated structure of the Barcelona Metropolitan Region as well as the Catalan territory, an increment of the influence of the identified sub-centres on the urban hierarchy at the time that these identified centres are more dominant in terms of in-commuting flows, more self-contained in comparison with the sub-centres that are detected by using the standard employment and demographic density functions.
Keywords: 330